Asymptomatic bacteriuria in HIV positive and negative pregnant women at Federal University Teaching Hospital Lafia: a comparative study - Dogara, Bawa D.; Lohnan, Changkat L.; Ozegya, Mohammed S.; Khadijat, Jibril A.; C. Mary, Momoh; Solomon, Audu E.; Chinedu, Okoro S.; Olabamiji, Adeola (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Pregnant women with asymptomatic bacteriuria (ASB) are at increased risk of complicated urinary tract infection. The prevalence and risk of progression may be higher with background human immunodeficiency viral (HIV) infection. The aim of the study was to compare the prevalent microbial isolates and antibiotic sensitivity pattern in asymptomatic bacteriuria among HIV positive and negative antenatal clients in Federal University Teaching Hospital (FUTH), Lafia. Methods: A cross sectional comparative study carried out among 60 HIV positive and negative antenatal women respectively at the obstetric unit of FUTH, Lafia, Nasarawa state. Relevant Socio-demographic and clinical data were collected using structured proforma. ‘Clean catch’ midstream urine samples were collected from each subject and microbial culture and sensitivity test were carried out and analysis done using SPSS version 22. A p-value of less than 0.05 was accepted as statistically significant. Results: The overall prevalence of ASB in both groups was 53.3% with a higher prevalence of 54.7% HIV positive compared to the prevalence of 45.3% in HIV negative pregnant women. Echerechia coli were the commonest organisms isolated and majority of the organism isolated were gram negative. Ciprofloxacin was the antibiotics with the best sensitivity. However, there is a marked resistance of greater than 50% of all the drugs. Conclusions: Though there is high prevalence of ASB in HIV positive women than the HIV negative pregnant women, there was no statistically significant difference in prevalence, microbial isolates and antibiotic sensitivity in the two groups.